Germline Genetic Modification and Identity: the Mitochondrial and Nuclear Genomes. (11th August 2017) - Scott, Rosamund; Wilkinson, Stephen
Abstract: In a legal 'first', the UK removed a prohibition against modifying embryos in human reproduction, to enable mitochondrial replacement techniques (MRTs), a move the Government distanced from 'germline genetic modification', which it aligned with modifying the nuclear genome. This paper (1) analyzes the uses and meanings of this term in UK/US legal and policy debates; and (2) evaluates related ethical concerns about identity. It shows that, with respect to identity, MRTs and nuclear genome editing techniques such as CRISPR/Cas-9 (now a policy topic), are not as different as has been supposed. While it does not follow that the two should be treated exactly alike, one of the central reasons offered for treating MRTs more permissively than nuclear genetic modification, and for not regarding MRTs as 'germline genetic modification', is thereby in doubt. Identity cannot, by itself, do the work thus far assigned to it, explicitly or otherwise, in law and policy.